2021
DOI: 10.1186/s43043-021-00062-7
|View full text |Cite
|
Sign up to set email alerts
|

Predictive factors of ovarian response to GnRH antagonist stimulation protocol: AMH and age are potential candidates

Abstract: Background Prediction of ovarian response prior to the ovarian stimulation cycle is useful in determining the optimal starting dose of recombinant follicle-stimulating hormone (r-FSH). This study was designed to (I) evaluate which of the following parameters (age, AMH, and FSH) can be used as a predictor of ovarian response to GnRH antagonist stimulation protocol, (II) determine the cutoff value of AMH and age for predicting poor and high ovarian response, and (III) investigate the relationship… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 43 publications
0
2
1
Order By: Relevance
“…Even though advancing age is considered a marker for declined response to ovarian stimulation, it does not affect all women equally. [ 9 ] In the present study, we did not find any significant difference between the PR and GR groups for patient parameters – age and BMI. The mean age of the GR and PR groups is 31.4 and 31.7 years, respectively.…”
Section: Discussioncontrasting
confidence: 55%
“…Even though advancing age is considered a marker for declined response to ovarian stimulation, it does not affect all women equally. [ 9 ] In the present study, we did not find any significant difference between the PR and GR groups for patient parameters – age and BMI. The mean age of the GR and PR groups is 31.4 and 31.7 years, respectively.…”
Section: Discussioncontrasting
confidence: 55%
“…However, these factors have limited predictive value. Therefore, emerging studies reported that the multivariate models predicted ovarian response, and found the model could improve the predictive power [ 17 , 59 - 61 ]. For example, Honnma et al [ 60 ] thought that serum AMH in combination with age is a better indicator than AMH alone.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, circulating AMH level appears to indicate the size of the standing pool of primordial follicle as seen in different studies [46][47][48][49]. Nevertheless, there are no such clear evidences regarding the correlation between AMH level and oocyte quality, whereas the age-related declination of follicular pool was observed to be an explanation of diminished oocyte quality [50,51]. Along with the number of primordial follicles, some endocrine parameters like FSH, estradiol, and inhibin B and ultrasonographic parameters like count of antral follicles and determination of ovarian volume are also considered as markers of ovarian reserve.…”
Section: Role Of Amh As a Marker Of Ovarian Reservementioning
confidence: 96%